Artistic composition of proverbs in Al-Bayan, Al-Tabin, and Al-Bakhla by Al-Jahiz - شقرة, لميس; هيفاء ديوب (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Proverbs constitute a special type of prose expression, especially in the works of the Arabs, who transformed these proverbs from life lessons into an expressive art in its own right. This was clearly demonstrated by Al-Jahiz in his two books, Al-Bakhla and Al-Bayan and Al-Tabyin. Each of the previous proverbs indicates a specific semantic concept that has a guiding role in the recipient’s behavior, urging him to benefit from the experiences of others. The proverb had clear foundations in my book Al-Jahiz, and it had psychological, social, and philosophical connotations that reflected a language capable of containing diverse human experiences. Al-Jahiz's construction of the proverb was not an arbitrary construction, but rather it was a functional construction in which he relied on the structural diversity evident in his artistic images, which were divided into metaphors, similes, and metonymies, and each of these images had a special structural structure. After the introduction, which introduced proverbs, the research was divided into three main headings: The first: was concerned with metaphor, and included examples of proverbs in which metaphor appeared in both its verbal and verbal types, and the second: was concerned with simile and included a number of examples in which the proverb was based on simile of its various types. The third: was concerned with the exquisite construction of proverbs, which included a number of sub-headings, namely: alliteration, counterpoint, and assonance. The models in the research titles were studied in an analytical study that highlighted the aesthetics of the studied phenomenon, then there was a conclusion that included the results of the research.